Cicero on artes liberales. Merits and Problems - Woldemar Görler (Ciceroniana On Line, 2020)
The expression artes liberales, found first in Cicero, has had a lasting and multiform impact through Seneca and Martanius Capella to our days. In its essence, the expression calls for a complete education (over and above strictly technical training) – a project which still has a bearing today with reference to Cice- ro. This is a credit to Cicero, but the project itself is not without issues. Liberalis does not mean “free”, as it is often translated today, but “worthy of a free man”, making it distinct from “dirty” money-making occupations. Such a limitation imposed upon an elite upper class is alien to us. In other instances, Cicero describes the same arts without reservation as “human” (humanae). They are the object of study for their own sake, insofar as they have an intrinsic value, and not to gain an advantage or benefit (such as to earn money). In this respect, the at- tributes liberalis and humanus are often interchangeable. Cicero includes in the artes liberales geometry, music, literature (and poetry), natural sciences, ethics, and politics. This programme is still valid today, though it presents some gaps such as the visual arts and foreign languages. The programme ought to, therefore, be completed and modified. Cicero regularly highlights that all the artes liberales share a common bond. This picture allows for different interpretations. It comes close to the allegory of a circle of noble arts, which is not mentioned in Cicero. However, even if there exist variations and modifications in form, image and con- tent of the artes liberales, Cicero’s reflections on the ideal education remain their original source and essence; they should therefore also be taken into account in current debates on education.